Panoramic Study on the Concept of Varna and Charakokta Varnya Mahakashaya (International Journal of Ayurveda and Pharma Research, 2024)
In today's society, beauty is a focal point of interest, with individuals often associating their physical appearance with self-esteem. Ayurveda being the ancient treatise has dealt regarding Tvacha and Varna as one of the important factors formed during intra-uterine life. Dravyas which help in promoting as well as restoring Varna or normal skin colour is termed as Varnya. Acharyas have dedicated separate Varga containing Dravyas that aids in Varnya action. Methods: Acharya Charaka in Sutrasthana 4th Chapter has resoluted Mahakashaya Varga among which Varnya Mahakashaya -Drugs which helps in restoring the Varna are mentioned. These Dravyas can be used for external application in the form of Lepa or can be taken internally in the form of Kashaya, Churna etc. Results: Dravyas present in Varnya Mahakashaya are predominant in Tikta and Madhura Rasa, Sheeta Virya. Flavonoides and triterpenoids present in these drugs possess anti-oxidant and anti-tyrosinase action that helps in inhibition of tyrosinase enzyme thereby controlling the release of melanin pigment. Depending upon the skin condition, Dravyas can be chosen wisely.